 Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping ```Solved Examples of Ellipse:

Example 1: Find the points on the ellipse x2 + 3y2 = 6 where the tangent are equally inclined to the axes. Prove also that the length of the perpendicular from the centre on either of these tangents is 2.

Solution:

The given ellipse is x2 + 3y2 = 6

Or x2/6 + y2/2 = 1 ...... (1)

If the coordinates of the required point on the ellipse (1) be (√6 cos Φ, √2 sin Φ) then the tangent at the point is x/√6 cos Φ + y/√2 sin Φ = 1 ...... (2)

Slope of (2) = (-cos Φ)/√6 ×√2/(sin Φ ) = (-√2)/√6 cot Φ

As the tangents are equally inclined to the axes so we have

-1/√3 cot Φ = + tan 45o = + 1

Hence, tan Φ = + 1/√3

The coordinates of the required points are

(±√6 × √3/2, ±√2 × 1/2) and (±√6 × √3/2, ±√2 × 1/2)

= (± (3√2)/2, ±1/√2) and (± (3√2)/2, ± 1/√2)

Again the length of perpendicular from (0, 0) and (2),

= (√6.√2)/√(2 cos2Φ + 6 sin2Φ)

= (2√3)/√((2.3/4) + (6.1/4) )

= (2√3)/√3

= 2.

Example 2:

If P be a point on the ellipse x2/a2 + y2/b2 = 2/c whose ordinate is √2/c, prove that the angle between the tangent at P and SP is tan-1 (b2/ac), where S is the focus.

Solution:

The given ellipse x2/a2 + y2/b2 = 2/c ...... (1)

If (x', √(2/c)) be the coordinates of the given point P on the ellipse (1).

Then the tangent at P will be: (xx')/a2 + (yy')/b2 = 1

(xx')/(a2(2/c)) + (yy' (√(2/c)))/(b2 (2/c)) = 1

The slope of tangent at P is (-b2 (2/c) x')/(a (2/c)(√2(2/c))) = m1 (say)

If S be the focus, then slope of PS =  y'/(x'+ae) =√(2/c)/(x' + a√(2/c)e)= m2 (say)

If angle between the focal distance SP and tangent at P is θ, then

tan θ = (m2 - m1)/(1 + m2 m1).

(a2 (2/c) + b2 x'2+ aeb2x' √(2/c))/((a2 x' + a3 e√(2/c) - b2x')√(2/c))

point (x',√(2/c)) lies on ellipse (1), we have

b2 x'2 + a2(2/c) = (2a2 b2)/c

and since a2 - b2 = a2 e2 so we have

(-(2a2 b2)/c + aeb2 x' √(2/c))/((a2e2x' + a2e√(2/c)) √(2/c)) = (√(2/c) ab2(√(2/c)

(a + ex')/(a2e(√(2/c)) a+ex')) √(2/c)) = b2/ae.

Hence, θ = tan-1 b2/ae.

Hence proved.

Example 3:

If P, Q, R are three points on the ellipse x2/a2 + y2/b2 = 1 whose eccentric angles are θ, Φ and Ψ then find the area of ΔPQR.

Solution:

The coordinates of the gives points P, Q, R on the ellipse x2/a2 + y2/b2 = 1, will be (a cos θ, b sin θ), (a cos Φ, b sin Φ) and (a cos Ψ, b sin Ψ).

Area of triangle PQR formed by these points

= 1/2 [x1y2 - x2y1 + x2y3 - x3y2 + x3y1 - x1y3]

= 1/2 [ab cos θ sin Φ - ab sin θ cos Φ + ab cos Φ sin Ψ - ab sin Φ cos Ψ + ab in θ cos Ψ - ab cos θ sin Ψ]

= 1/2 ab [2 sin(Φ-θ)/2 cos (Φ-θ)/2 + 2 sin (Ψ-Φ)/2 cos (Ψ-Φ)/2 + 2 sin (θ-Φ)/2 cos (θ-Φ)/2]

= ab sin (θ-Φ)/2 (cos (θ + Φ + 2Ψ)/2 cos(Φ-θ)/2)

= 2ab sin (θ-Φ)/2 cos (Φ-Ψ)/2 cos (Ψ-θ)/2.

Example 4:

Find the locus of the extremities of the latus recta of all ellipses having a given major axis 6a.

Solution:

Let LSI be the latus rectum, C be the centre of the ellipse and the coordinates of L be (x, y) then x = CS = 3 ae ...... (1)

And y = SL = b2/3a = (9a2(1 - e2))/3a = 3a (1 - e2) ...... (2)

Eliminating the variable 'e' from (1) and (2) we get the locus of L.

Hence putting the value of e from (1) and (2), we get

y = 3a(1-x2/9a2)

⇒ x2 = 9a2 - 3ay

⇒ x2 = 3a(3a - y), which is clearly a parabola. Similarly we can show that the locus of L' is x2 = 3ay(y + 3a) which is again a parabola.

Example 5:

Find the equation of the normals at the end of the latus rectum of

the ellipse x2/a2 + y2/b2 = c2 and find the condition when each normal through one end of the minor axis.

Solution:

The ellipse x2/a2 + y2/b2 = c2

⇒ x2/(a2 c2 + y2/(b2 c2) = 1 ...... (1)

Then the end point of the latus rectum is (ace,(b2 c)/a)

The normal at this point will be

(x-ace)/(ace/(a2 c2)) = (y-b2 c/a)/((b2 c/a)/(b2 c2))

⇒ ((x-ace))/e ac = (y-(b2 c)/a) ac

⇒ (x-ace)/e = y-(b2 c)/a

If this normal passes through (0, - bc), then, we have

(-ace)/e = -bc-b2/a c

⇒ a = b + a(1 - e2)

⇒ b - ae2 = 0

⇒ b/1-e2 ⇒ b2/a2 = e4

⇒ e4 + e2 = 1. This is required condition.

Example 6:

The circle x2 + y2 = 4 is concentric with the ellipse x2/7 + y2/3 = 1; prove that the common tangent is inclined to the major axis at an angle 30o and find its length.

Solution:

The ellipse x2/7 + y2/3 = 1 ...... (1)

The equation to the circle is

x2 + y2 = 4 ...... (2)

As the line y = mx + √(a2m2 + b2)

i.e. y = mx  + √(7m2 + 3) ...... (3)

is always the tangent on the ellipse. If this is also a tangent on the circle (2) then length of perpendicular from the centre (0, 0) on the line (1) must be equal to the radius of circle i.e. 2.

Hence, √(7m2  + 3)/√(1+ m2) = 2

⇒ 7m2 + 3 = 22(1 + m2)

⇒ 7m2 - 4m2 = 4 - 3

⇒ m2 = 1/3

⇒ m = + 1/√3

Hence the common tangent to the two curves is inclined at an angle of tan-1 (+1/√3) i.e. 30o to the axis.

Note:

We can also prove the above result by using the fact that the line = mx + √(7m2+3) will be tangent to x2 + y2 = 4 if discriminant of x2 + (m + √(7m2 + 3))2 = 4 is zero.

Let P and Q be the points of contact of the common tangent with ellipse and circle respectively and O be the common centre of the two, then

PQ = √(OP2 - OQ2) [∠CPQ = 90o]

The coordinates of P are [(-a2m)/√(a2m2 + b2), b2/√(a2m2 + b2)]

i.e. [(-7/√3)/√(16/3), 3/√(16/3)]

i.e.[(-7)/4,(3√3)/4]

and coordinate of O are (0, 0)

So, OP = √(((-7)/4)2 + ((3√3)/4)2) = √(19/4)

As OQ = r = 2

.·. PQ = √(OP2 - OQ2) = √(19/4 - 4) = √3/2

Example 7:

If q be the angle between CP and normal at point P, on the ellipse a2x2 + b2y2 = 1, then find out tan θ and prove that its greatest value is (b2-a2)/2ab. C is centre of ellipse and P is any point on ellipse.

Solution:

The equation of the ellipse be

x2/(1/a2) + y2/(1/b2)  = 1 ..... (1)

If θ be the angle between the normal at P = (1/a cos Φ, 1/b sin Φ and PC where C is the centre of the ellipse given by (1) equation to the normal PG is

x/a sec Φ - y/b cosec Φ = 1/a2 -1/b2

⇒ bx sec Φ - ay cosec Φ = (b2 - a2)/ab

Its slope = (b sec Φ)/(a cosec Φ) = b/a tan Φ = m1 (say)

The slope of PC = (1/b sin Φ)/(1/a cos Φ) = a/b tan Φ = m2 (say)

tan θ = (m1 - m2)/(1 + m1m2)

= (a/b tan Φ – a/b tan Φ)/(1 + (b/a) tan Φ (a/b) tan Φ)

= ((b2- a2) tan Φ) /ab(1 – tan2 θ)

= (b2 - a2)/2ab. (2tanΦ)/(1 – tan2 Φ)

tan θ = (b2 - a2)/2ab sin 2Φ

The value of tan θ will be maximum when sin 2Φ is maximum, sin 2Φ is maximum i.e. sin 2Φ is 1. Therefore the greatest value of tan θ is (b2-a2)/2ab.

Example 8:

Find the locus of the point of intersection of the two straight lines (x tan α)/a - y/b + tan x = 0 and x/a + (y tan α)/b where a is fixed angle. Also find the eccentric angle of the point of intersection.

Solution:

Equation of the lines are given as

(x tan α)/a – y/b + tan α = 0 ...... (1)

x/a + (y tan α)/b - 1 = 0 ...... (2)

To find the locus of the point of intersection, we have to eliminate the variable 'tan a' from (1) and (2), so by (2),

y/b = 1/(tan α) (1 – x/a) and by (1)

y/b = tan α (1 + x/a)

Multiplying we get

(y/b)2 - (1 – x/a)(1 + x/a)

⇒ x2/a2 + y2/b2 = 1

This is the equation of an ellipse

Again solving (1) and (2), we get

x = a (1 – tan2α)/((1 + tan2α))

x = a(1 – tan2α)/(sec2α)

Let the abscissa of the point of intersection be a cos φ, then

x = a cos φ = a(1 – tan2 α)/(sec2 α)

⇒ cos φ = (1 – tan2 α)/(sec2 α)

⇒ (1 – cos φ )/(1 + cos φ) = (sec2α – (1 – tan2α))/(sec2α + (1 – tan2α)) (By components & dividendo)

= (2 tan2 α)/2 = tan2α

⇒ (2 sin2φ/2)/(2 cos2 φ/2) = tan2 α

⇒ tan2 φ/2 = tan2 α

⇒ tan φ/2 = tan α

Hence φ = 2α.

Example 9:

If TP and TQ are perpendiculars upon the axes from any point T on the ellipse x2/a2 + y2/b2 = 4. Prove that PQ is always normal to fixed concentric ellipse.

Solution:

The ellipse is given by x2/(4a2) + y2/(4b2) = 1 ...... (1)

If the co-ordinates of T on the ellipse be (2a cos φ, 2b sin φ) an TP and TQ perpendiculars on x-axis and y-axis respectively, the co-ordinates of P and Q will be (2a cos φ, 0) and (0, 2b sin φ) respectively.

Now equation of PQ is

y - 0 = (2b sin φ – 0) /(0 – 2a cos φ)(x - 2a cos φ)

⇒ x/(2a cos φ) + y/(2b sin φ) = 1

⇒ x/a sec φ + y/b cosec φ = 2 ...... (2)

Now equation to the normal at point (A cos φ, B sin φ) with respect to any other concentric ellipse x2/A2  + y2/B2 = 1 is

Ax sec φ - By cosec φ = A2 - B2 ...... (3)

As (2) and (3) are similar, on comparing then we have,

A/(1⁄2a) + B/(1⁄2b) = A2 - B2 ...... (4)

Solving the two equations given by (4), we get

B = (2a2b)/(a2 - b2) and A = (-2ab2)/(a2 - b2)

So the line (2) i.e. x/2a sec φ + y/2 cosec φ = 1 is a normal to the fixed ellipse x2/A2 + y2/B2.

Where A = (-ab2)/(a2-b2)and B = (a2b)/(a2-b2).

Example 10:

If the straight line y = 2x + 2 meets the ellipse 2x2 + 3y2 - 6, prove that equation to the circle, described on the line joining the points of intersection as diameters, is 7x2 + 7y2 + 12x - 4y - 5 = 0.

Soluion:

The line is given as y = 2x + 2 ...... (1)

and the ellipse is given as x2/a2 + y2/b2 = 1 ...... (2)

Solving (1) and (2), we get

x2/3 + (2x + 2)2/b2 = 1

⇒ x2/3 + 2(x2 + 2x + 1) = 1

⇒ 7x2 + 12x + 6 = 3

⇒ 7x2 + 12x + 6 = 3

Let x1 and x2 be the two roots of this equation.

x1 + x2 = -12/7 ...... (3)

and x1x2 = 3/7 ...... (4)

Let y1 and y2 be the corresponding ordinates for the abscissa x1 and x2; so the co-ordinates of the points of intersection will be (x1, y1) and (x2, y2).

As these lie on line y = 2(x + 1)

We have y1 = 2(x1 + 1) and y2 = 2(x2 + 1)

Where y1 + y2 = 2(x1 + x2) + 4 ...... (5)

y1y2 = 4(x1 + 1) (x2 + 1) ...... (6)

The equation to the circle drawn with the line joining (x1, y1) and (x2, y2) as diameter is

(x - x1) (x - x2) + (y - y1) (y - y2) = 0

⇒x2 + y2 - x(x1 + x2) - y(y1 + y2) + x1x2 + y1y2 = 0

⇒  x2 + y2 - x(x1 + x2) – y [2(x1 + x2) + 4] + x1x2 + 4[x1x2 + (x1 + x2) + 1] = 0 ( using (5) and (6))

Putting the values from (3) and (4)

x2 + y2 - x (-12/7) - y[2(-12/7) + 4] + 3/7 + 4[3/7 + (-12/7) + 1] = 0

which gives 7x2 + 7y2 + 12x - 4y - 5 = 0. Hence proved.

Example 11:

If the product of the perpendiculars from the foci upon the polar of P be constant and equal to c2. Find the locus of P.

Solution:

Suppose the equation to the ellipse x2/a2 + y2/b2 = 1. The co-ordinate of foci are (ae, 0) and (-ae, 0).

Let the co-ordinates of P be (h, k). Then polar of P is xh/a2 + yk/b2 = 1

Or b2xh + a2yk - a2b2 = 0 ...... (1)

If P1 and P2 be the lengths of the perpendiculars on the line (1) from (ae, 0) respectively are

P1 = (b2hae – a2b2) /√(b2h2 + a4k2)

And P2 = (-a2b2 - b2hea)/√(b2h2 + a4x2)

.·. P1P2 = (-b2h2a2e2 + a4b4)/(b4h2 + a4) = c2 (By hypothesis)

⇒ a4b4 - b4h4a2e2 = c2b4h2 - c2a4k2

⇒b4h2 (c2 + a2e2) + c2a4k2 = a4b4

Generalizing the locus of the point P(h, x) is

b4 x2 (c2 + a2e2) + c2a4y2 = a4b4

Example 12:

Chords of ellipse x2/a2 + y2/b2 = 1 always touch another concentric ellipse x2/α2 + y2/β2 = 1, show that the locus of their poles is (α2x2)/a2 + (β2y2)/b2 = 1.

Solution:

Let (x1, y1) be the pole of a chord of the ellipse x2/a2 + y2/b2 = 1 ...... (1)

Then the equation of this cord is the same as the polar of (x1, y1) with respect to (1)

i.e. xx1/a2 + yy1/b2 = 1 ...... (2)

If (2) touches the ellipse x2/α2 + y2/β2 = 1, then (b2/y1)2 = α2{-{b2x1/a2y1}}2 + β2

⇒ b4/y12 = (α2b4x12/a4y12) + β2

⇒ (α2x12)/a4 + (β2y12)/b4 = 1

.·. The locus of (x1, y1) is (α2x2)/a2 + (β2y2)/b4 = 1

Hence proved.

Example 13:

If the straight line y = x tan θ + √((a2 tan2θ + b2)/2), θ being the angle of inclination, intersects the ellipse x2/a2 + y2/b2 = 1, then prove that the straight lines joining the centre to their point of intersection are conjugate diameters.

Solution:

The equation of the ellipse be

x2/a2 + y2/b2 = 1 ...... (1)

and equation to the line is given as

y = x tan θ + √((a2tan2θ + b2)/2), θ being angle of inclination.

We can write this equation as y = mx + √((a2m2 + b2)/2)

⇒ ((y-mx)/√2)/√(a2m2 + b2 ) = 1 ...... (2)

To get the equation to the lines joining the point of intersection to the origin, making (1) homogeneous with the help of (2), we have

x2/a2 + y2/b2 = [((y-mx)/√2)/√(a2m2 + b2)]2 = 2((y2 + m2x2 - 2mxy))/(a2m2 + b2)

⇒ (b2x2 + a2y2) (a2m2 + b2) = 2a2 b2(y2 + m2x2 - 2mxy)

y2 a2(a2m2 - b2) + 4m2 - b2xy - b2x2 (a2m2 - b2) = 0

⇒ y2 + (4mb2)/((a2m2 + b2)) xy – b2/a2x2 = 0 ...... (3)

This equation represents two straight lines y = m1x and y = m2x then the combined equation will be y2 - (m1 + m2)xy + m1m2x2 = 0.

Comparing (3) and (4); we get

m1m2 = -b2/a2 which is the condition of diameter to be conjugate. Hence the lines are the conjugate diameters.

Example 14:

The eccentric angles of two points P and Q on the ellipse Φ1, Φ2. Find the area of the parallelogram formed by the tangents at the ends of diameters through P and Q.

Solution:

The ellipse is x2/a2 + y2/b2 = 1

Equation to the tangent at the points P and Q are

x/a cos Φ1 + y/b sin Φ1 = 1 ...... (1) and

x/a cos Φ2 + y/b sin Φ2 = 1 ...... (2)

Solving (1) and (2), we will have the coordinates of the point of intersection. Multiplying (1) by sin Φ2 and (2) by sin Φ1 and subtracting, we get

x/a (sin Φ2 cos Φ1 - cos Φ2 sin Φ1) = sin Φ2 - sin Φ1

⇒ x/a sin (Φ2 - Φ1) = 2 sin (Φ2 - Φ1)/2 cos (Φ2 + Φ1)/2

.·. x = a (cos((Φ1 - Φ2)/2))/(cos(Φ1 - Φ2)/2) and y = b (sin(Φ1 + Φ2)/2)/(cos (Φ1 - Φ2)/2)

Above are co-ordinates of the point of intersection L of tangents at p and Q, i.e. at Φ1 and Φ2.

Putting Φ1 = p + Φ1 in above we get the co-ordinates of the point of intersection M of tangent at Q and P' as

Area of the parallelogram LMNO = 4ΔCLM

= 4.1/2 (x1y1 - x2y2)

= 2 ab/(sin (Φ1 - Φ2)/2 cos (Φ1 - Φ2)/2) [- cos2 (Φ1 + Φ2)/2 -sin (Φ1 + Φ2)/2]

= (-4ab)/(sin(Φ1 - Φ2))

= - 4ab cosec (Φ1 - Φ2) Area can't be (-) ve

So the area = 4ab cosec (Φ1 - Φ2).

Related Resources:

For getting an idea of the type of questions asked, refer the previous year papers.

To read more, Buy study materials of Ellipse comprising study notes, revision notes, video lectures, previous year solved questions etc. Also browse for more study materials on Mathematics here.
```  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution 